Multi-layer TCP/IP Protocol Stack Configuration to Enhance QoS in MANET - Prathviraj N, Santosh L Deshpande, Sayinath Udupa* (International Journal of Advanced Science and Technology, 2020)
The wide range of applications running on Mobile Ad-hoc NETwork (MANET) demands a diversified set of network characteristics from all participating nodes. The network characteristics are collective information from all layers of the TCP/IP protocol stack. The information such as various applications Quality of Service (QoS) requirement in application layer depends upon latency and end to end throughput at the transport layer, node throughput at the data link layer and finally bandwidth and SNR from the physical layer. The effectiveness of message delivery is analyzed with QoS in overall packet delivery, for which information from all layers collectively taken into account. The TCP/IP protocol stack is rigid and interacts only with its neighboring layers, this makes collaborating with all layers non-existent. Multilayer TCP/IP protocol stack configuration is proposed to overcome strict layering paradigm by allowing interaction with multiple layers. The proposed solution can be extended for QoS routing based on applications running and network characteristics dynamically.